Analysis of PPL Implementation in The Prajabatan PPG Program In The Field of Sociology Studies At SMA Negeri 1 Pontianak - Suriyanisa, Suriyanisa; Yani, Yani; Rajab, Siti Chintya Wulan; Wijaya, Tri; Syamsuri, Syamsuri; Ramadhan, Iwan (Universitas Tanjungpura, 2024)
This research aims to identify the effectiveness of implementing Field Experience Practices (PPL) in developing the competency of Pre-Service Teacher Professional Education Program (PPG) students at SMA Negeri 1 Pontianak. The relevance of this research lies in its contribution to improving the quality of learning in schools and preparing Pre-Service PPG students to become competent teachers and ready to face the dynamics of the world of education. This research method uses a descriptive qualitative approach through data collection techniques through observation, interviews, and document analysis. The research population was PPL PPG students in the field of Sociology studies at SMA Negeri 1 Pontianak, the research informants were 3 students. Effective PPL allows students to develop analytical, reflective skills and teacher identity through field interaction, observation and reflection. Even though they face obstacles such as limited schedules, effective communication between students and the school can overcome them. PPL plays an important role in forming competent and professional teachers in the future. Thus, this research provides recommendations for increasing the effectiveness of PPL implementation, including by optimizing communication between students and school officials, arranging flexible schedules, and increasing the availability of facilities at schools. By overcoming these obstacles, it is hoped that the implementation of PPL can run more effectively and efficiently so that students can develop competence as prospective teachers who are ready to face the dynamics of the world of education.